2010
DOI: 10.1073/pnas.1013176107
|View full text |Cite
|
Sign up to set email alerts
|

Brain plasticity related to the consolidation of motor sequence learning and motor adaptation

Abstract: This study aimed to investigate, through functional MRI (fMRI), the neuronal substrates associated with the consolidation process of two motor skills: motor sequence learning (MSL) and motor adaptation (MA). Four groups of young healthy individuals were assigned to either (i) a night/sleep condition, in which they were scanned while practicing a finger sequence learning task or an eight-target adaptation pointing task in the evening (test) and were scanned again 12 h later in the morning (retest) or (ii) a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
247
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(277 citation statements)
references
References 39 publications
27
247
3
Order By: Relevance
“…However, this has not been supported by previous neuroimaging studies, which mostly show a decrease in cerebellar activity during learning and automaticity (Imamizu et al 2000;Doyon et al 2002;Penhune and Doyon 2005;Balsters and Ramnani 2011). This could relate to the decreases in complex and simple spikes seen in electrophysiology studies of the cerebellum during skill acquisition (Gilbert and Thach 1977;De Zeeuw and Yeo 2005;Medina and Lisberger 2008;Lepora et al 2009), or it could suggest that the cerebellum is involved in adapting and tuning cortical processes but does not act as a storage for these processes (Doyon et al 2003;Debas et al 2010). This is an area that requires further investigation, and we would suggest that future studies investigate cortico-cerebellar connectivity ( possibly using dynamic causal modeling) to try and establish how neocortical and connected cerebellar areas interact during learning (Apps et al 2009;Saalmann et al 2009).…”
Section: Differences In Processing First-and Second-order Rules In Thmentioning
confidence: 38%
“…However, this has not been supported by previous neuroimaging studies, which mostly show a decrease in cerebellar activity during learning and automaticity (Imamizu et al 2000;Doyon et al 2002;Penhune and Doyon 2005;Balsters and Ramnani 2011). This could relate to the decreases in complex and simple spikes seen in electrophysiology studies of the cerebellum during skill acquisition (Gilbert and Thach 1977;De Zeeuw and Yeo 2005;Medina and Lisberger 2008;Lepora et al 2009), or it could suggest that the cerebellum is involved in adapting and tuning cortical processes but does not act as a storage for these processes (Doyon et al 2003;Debas et al 2010). This is an area that requires further investigation, and we would suggest that future studies investigate cortico-cerebellar connectivity ( possibly using dynamic causal modeling) to try and establish how neocortical and connected cerebellar areas interact during learning (Apps et al 2009;Saalmann et al 2009).…”
Section: Differences In Processing First-and Second-order Rules In Thmentioning
confidence: 38%
“…It is possible that the aftereffect of cerebellar tDCS, which can last for up to 30 min after stimulation is over [33], could be directly enhancing consolidation processes. However, although the cerebellum may be involved in the consolidation of adaptation skills [53,54], consolidation of motor sequence tasks seem to be more dependent on the striatum [55] and/or M1 [56] while the cerebellum may be more crucial for early learning [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, how and whether offline periods of sleep and wakefulness respectively contribute to the consolidation of motor sequence learning remain a matter of debate. Whereas several studies have found that postlearning sleep contributes to the consolidation or stabilization of elementary motor skills in young adults (Barakat et al, 2011;Debas et al, 2010;Fischer, Hallschmid, Elsner, & Born, 2002;Smith & MacNeill, 1994), results are more controversial in the domain of visuomotor sequence learning. For instance, sleep-dependent consolidation and offline performance improvement were found for context-related (Spencer, Gouw, & Ivry, 2007;Spencer, Sunm, & Ivry, 2006) and goal-related (Cohen & Robertson, 2007;Cohen, Pascual-Leone, Daniel, & Robertson, 2005) components of an incidentally learned sequence.…”
Section: Introductionmentioning
confidence: 95%